2020
DOI: 10.1002/bmc.4837
|View full text |Cite|
|
Sign up to set email alerts
|

Determination of toosendanin and trans‐anethole in Fructus Meliae Toosendan and Fructus Foeniculi by HPLC–MS/MS and GC–MS/MS in rat plasma and their potential herb–herb interactions

Abstract: Ethnopharmacological relevance The objective of traditional Chinese medicine (TCM) combination theory is to “reduce toxicity and increase efficiency”, especially to solve the liver toxicity of many TCMs. Fructus Meliae Toosendan (CLZ)–Fructus Foeniculi (XHX) is a typical traditional Chinese herb pair that decreases the toxicity and increases the efficiency of the herbs. Fructus Meliae Toosendan (CLZ, cold‐natured) has significant liver toxicity. However, it has been widely used in combination with Fructus Foen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…R. rubescens has excellent anti-tumor effects against a variety of cancers [ 9 ]. R. rubescens not only greatly improves the anti-tumor effect of chemotherapy drugs but also reduces the required dosage and side effects [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…R. rubescens has excellent anti-tumor effects against a variety of cancers [ 9 ]. R. rubescens not only greatly improves the anti-tumor effect of chemotherapy drugs but also reduces the required dosage and side effects [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…After the combination use of trans -anethole, the C max (294.8 ± 92.01 ng/L), AUC (0–t) (347.2 ± 128.7 ng/Lh), AUC (0–∞) (475.6 ± 210.8 ng/Lh), MRT (0–t) (2.667 ± 0.989 h), and MRT (0–∞) (5.386 ± 2.886 h) of TSN were decreased significantly, while the values of V z/F (8.110 ± 5.502 L/kg) were notably increased. These outcomes indicated that co-administration of trans -anethole can decrease the absorption and bioavailability of TSN and shorten the elimination process of TSN, which reduced the risk of toxicity accumulation ( Yu et al, 2020 ).…”
Section: Pharmacokinetics Of Limonoidsmentioning
confidence: 99%
“…Quercetin, a natural flavonoid with marked antioxidant ability, was validated to alleviate liver injury caused by TSN, which provided a new insight into compatibility detoxification of drugs ( Jin Y. et al, 2019 ). In addition, fructus foeniculi, a typical detoxification drug for toosendan fructus, was reported to eliminate the toxicity of TSN by decreasing the absorption and bioavailability and accelerating the elimination process ( Yu et al, 2020 ).…”
Section: Toxicity Of Limonoidsmentioning
confidence: 99%
“…and Fructus Meliae Toosendan (mature fruit of Melia toosendan Sieb. et Zucc) are two herbs used in combination in traditional Chinese medicine, and pharmacokinetic studies have revealed that Fructus Foeniculi attenuates the hepatotoxicity exerted by Fructus Meliae Toosendan via decreasing its absorption and increasing elimination thereby decreasing in vivo accumulation of the toxic constituent, toosendanin [162]. However, there is a possibility of occurring undesirable alterations of pharmacokinetics upon concomitant administration of different herbs especially in the case of introducing novel herbal mixtures.…”
Section: Toxicity Concerns Of Herbal Medicines Targeting β-Cellsmentioning
confidence: 99%